Utilization of Blended Learning Methods Among Informatics Education Students of Citra Bangsa University - Cascia Selan, Agnes Rita; Sogen, Maria Magdalena B; Tahu, Christina Deryanti; Djumetan, Hesber; Kehi, Margaretha Andini (JUPE : Jurnal Pendidikan Mandala, 2025)
This study aims to disseminate Blended Learning among students of the Informatics Education Study Program, Citra Bangsa University. This study was conducted on students in semesters 2, 4, and 6 of the Informatics Education Study Program. The approach used is descriptive qualitative with a Likert scale as an instrument to measure the extent to which the Blended Learning method can be beneficial. The results of this study indicate that most responded positively to this method, especially in terms of ease of access to digital lectures and marriage, although some students still experience technical problems.